Synthesis and biological evaluation of a water-soluble derivative of the potent V-ATPase inhibitor archazolid - Persch, Elke; Menche, Dirk (Bioorganic & medicinal chemistry letters, 2012)
The water-solubility of the highly potent V-ATPase inhibitors archazolid A and the glucosylated derivative archazolid C was studied in the presence of a wide range of cosolvents, revealing very low solubilites. The first water-soluble analogue was then designed, synthesized, and evaluated for V-ATPase inhibitory activity in vitro.